The correct name for Oxyurichthys longicauda Steindachner and a few other errors - Larson, Helen K.; Pezold, Frank L. (Zootaxa, 2016)
In 2015, Pezold and Larson published a revision of the gobiid genus Oxyurichthys, and made an error in their use of the name O. uronema (Weber) for one of the species. The reasons for this would make a fine example of one of Evenhuis’ taxonomic impediments to nirvana (2007). Pezold and Larson first considered collaborating on this work in 1983, but this did not happen until nearly a decade later. Intensive work began in 1996; by then Larson had examined syntypes of both species in 1988 and determined that Gobius uronema Weber, 1909, was the same species as Gobius longicauda Steindachner, 1893.